Efficacy of cefoxitin for the treatment of urinary tract infection due to extended-spectrum-beta-lactamase-producing Escherichia coli and Klebsiella pneumoniae isolates. (January 2019) - Senard, Olivia; Bouchand, Frédérique; Deconinck, Laurene; Matt, Morgan; Fellous, Lesly; Rottman, Martin; Perronne, Christian; Dinh, Aurélien; Davido, Benjamin
Introduction: Cefoxitin has a good in vitro activity and stability in resistance to hydrolysis by extended-spectrum beta-lactamases and is a good candidate for the treatment of urinary tract infection. However, data are scarce regarding its use in clinical practice. Methods: We conducted a retrospective study from September 2014 to November 2017, in a tertiary care hospital in Garches (France). We gathered all prescriptions of cefoxitin for urinary tract infection due to extended-spectrum beta-lactamase isolates. We compared the clinical outcomes between Escherichia coli and Klebsiella pneumoniae extended-spectrum-beta-lactamase-producing isolates after a 90-day follow-up. When available, we assessed whether cefoxitin-based regimen was associated with an emergence of resistance. Results: The treatment of 31 patients with a mean age of 60 ± 18 years was analyzed. We observed a clinical cure of 96.7% ( n = 30/31) at day 30 and of 81.2% ( n = 13/16) and 85.7% (12/14) at day 90 for extended-spectrum beta-lactamase Escherichia coli and Klebsiella pneumoniae isolates, respectively ( p = 0.72). No adverse events were reported. One patient who relapsed carried a Klebsiella pneumoniae isolate that became intermediate to cefoxitin in the follow-up. Conclusion: In a period of major threat with a continuous increase of extended-spectrum beta-lactamase obliging to a policy of carbapenem-sparing regimens, it seems detrimental to deprive physicians of using cefoxitin for extended-spectrum beta-lactamase Enterobacteriaceae for the treatment of urinary tract infection while our data show its efficacy.